C-Band Linear Polarization Metasurface Converter with Arbitrary Polarization Rotation Angle Based on Notched Circular Patches - Tao Zhang; Haoran Wang; Chongmei Peng; Zhaohui Chen; Xiaoyi Wang (Crystals, 2022)
This paper presents a linear polarization metasurface converter with arbitrary polarization rotating angle and stable oblique incident response, which is based on the concept of linear-to-circular polarization decomposition and recombination. A metasurface unit cell is proposed using a notched circular patch with two metallized vias connected to the bottom-layer coplanar waveguide (CPW) transmission lines. By changing the length of the two transmission lines, different polarization rotation angle may be realized. The proposed metasurface polarization converter is theoretically analyzed and full-wave simulated. A <semantics>45∘</semantics> metasurface polarization converter with <semantics>8×8</semantics> unit cells is designed and experimentally demonstrated. The experimental results agree well with the simulation, showing that the proposed metasurface polarization converter can achieve a high polarization conversion ratio (PCR) larger than <semantics>85%</semantics> under up to <semantics>50∘</semantics> oblique incident wave.